1988
DOI: 10.1103/physrevlett.61.621
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant Field-Induced Spin-Density-Wave Transitions

Abstract: We have used magnetotransport measurements to determine the phase diagram of (TMTSF>2C104 from 0.5 to 10 K in magnetic fields to 30 T. This organic metal becomes a spin-density-wave semimetal as temperature is reduced in a magnetic field greater than a threshold field H c (T=0) -3 T. The critical temperature T C (H) increases with field in agreement with present theories, and reaches a maximum of 5.6 K at 18 T. Above this field, however, T C (H) decreases, extrapolating to zero temperature at 17 T. This reentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…The temperature-field phase diagram of the relaxed ͑TMTSF͒ 2 ClO 4 was first obtained, at ambient pressure, by Naughton et al 13 The authors found an unexpected feature: in the high magnetic field regime ͑H Ͼ 27 T͒, the FISDW phase is destroyed and a reentrant metallic state appears ͑dotted line in Fig. 1͒.…”
Section: A Experimental Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The temperature-field phase diagram of the relaxed ͑TMTSF͒ 2 ClO 4 was first obtained, at ambient pressure, by Naughton et al 13 The authors found an unexpected feature: in the high magnetic field regime ͑H Ͼ 27 T͒, the FISDW phase is destroyed and a reentrant metallic state appears ͑dotted line in Fig. 1͒.…”
Section: A Experimental Resultsmentioning
confidence: 90%
“…Indeed, at 0.5 K, a stable quantum Hall-semimetal phase corresponding to N = 1 plateau was observed from 7.5 to 27 T. 13,15,16 This plateau is somewhat spoiled above 15 T and shows, at high temperatures, besides oscillations, a slight accident at 17 T, which disappear above 3 K. 19 At 0.5 K, the very high field insulating state ͑SDWII phase in Fig. 1͒ is characterized by a nonquantized Hall resistance, 13,15,16 which is reminiscent of a N = 0 SDW phase. It seems, therefore, that the subphases SDWIII and SDWIV may be indexed with N = 1 while the SDWII may correspond to the N = 0 phase.…”
Section: A Experimental Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…A cascade of phase transitions into field-inducedspin-density-wave ͑FISDW͒ phases occurs at fields above 4 T. Near 15 T the second-order FISDW transition temperature reaches a maximum of Ϸ5.5 K. Another phase boundary is present at B RE ϳ28 T, and the high-field state ͑HFS͒ above B RE is also known as the reentrant phase. 2 Recently extensive studies of transport and magnetization have indicated that the B RE line is not connected to the second-order FISDW line, and hence the HFS is not a reentrant metallic state. 3 Aside from the complication of the B RE phase boundary, the HFS strongly represents the final Nϭ0 nested state predicted by the ''standard model.''…”
mentioning
confidence: 99%
“…-Specific-heat measurements on (TMTSF)&C104 have given thermodynamic evidence for the main SDW gap, but deviations from a siinple weakcoupling picture arise [7]. In (TMTSF)2C104, a number of anomalies become apparent in transport [8,9], magnetization [10], specific-heat [11], and thermopower [12] measurements.…”
mentioning
confidence: 99%